Augmented Reality sebagai Media Pembelajaran Interaktif 3D untuk Meningkatkan Motivasi Belajar Siswa Digital Native - Yuvita Dela Carolina (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
This best practice aims to describe the use of Augmented Reality (AR) as a 3D interactive learning media that has an impact on increasing the learning motivation of digital native students. AR is a technology that can integrate the dimensions of the virtual world with the real world that can be displayed in real time. AR is implemented to convey the earth's material as a planet class X IPS 1 and X IPS 2 at SMA N 2 Wates. The method in writing this best practice uses a qualitative descriptive approach, with the stages in this best practice activity consisting of the preparation stage, implementation stage and evaluation stage. The author gives a questionnaire to students related to the evaluation of the use of AR which is then analyzed and used as the basis for determining conclusions. Based on the results of the questionnaire, it is known that there is an increase in students' learning motivation in participating in geography learning using AR as a 3D interactive learning medium, from before there were no students who had high motivation, after using AR as a medium 65% of students had very high motivation. In addition, students who have high motivation before using AR are only 3% to 23% of students, using five indicators of student learning motivation assessment, namely the desire to succeed, awareness in learning, persevering in completing assignments, never giving up when facing difficulties, interest in learning. in study. Based on these indicators, it is known that students' learning motivation has increased after using AR. Thus, it can be concluded that AR as a 3D interactive media can increase the learning motivation of digital native students.